Geometria extrínseca de superfícies singulares de R3 - Cruz, Douglas Hilário da (2013)
In this work we study asymptotic lines in the neighborhood of a singular point, lines of curvature in the neighborhood of singular curves of ellipsoid wave fronts and the lines of curvature in the neighborhood of the Darbouxian umbilic points.